2012
DOI: 10.1364/oe.20.001963
|View full text |Cite
|
Sign up to set email alerts
|

Integral volumetric imaging with dual layer fly-eye lenses

Abstract: This paper proposes an integral volumetric imaging system that uses a coarse fly-eye lens and a fine fly-eye lens to show smooth and deep 3D image. Conventional integral volumetric imaging displays using a coarse fly-eye lens have suffered from low image quality due to distinct seam of lenses and moiré pattern caused by layered panel structure. To solve these problems the proposed system uses a fine fly-eye lens whose elemental lens has a long focal distance. By placing a fine fly-eye lens near the layered rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Though occasional defects are observed in Figure 3 (b), uniform coating of PMMA spheres has been achieved on a larger scale. As the moth-eye lens structure has been proved to be an effective way for light redistribution [11]- [13], here, the micro-lens array combination of layer ②-④ can contribute to the uniformity of the light from adjacent pixels and the removal of pixelation.…”
Section: Resultsmentioning
confidence: 99%
“…Though occasional defects are observed in Figure 3 (b), uniform coating of PMMA spheres has been achieved on a larger scale. As the moth-eye lens structure has been proved to be an effective way for light redistribution [11]- [13], here, the micro-lens array combination of layer ②-④ can contribute to the uniformity of the light from adjacent pixels and the removal of pixelation.…”
Section: Resultsmentioning
confidence: 99%
“…system in a floating setup, the degradations, such as image distortions, can be suppressed with enhanced depth expression [60]. It has also been reported that the moiré and seam noises between the adjacent lenses can be effectively removed using multiple lens arrays with fine and coarse lenslets [61]. A recent study reported an integral floating system with modified elemental-image backlight and a thick lens array [62].…”
Section: Integral Floating Displaysmentioning
confidence: 99%
“…Integral imaging, also known as integral photography, was first proposed by Lippmann [1] in 1908. It is regarded as one of the most attractive approaches because of advantages such as full-color and real-time display of a 3D image within a certain continuous viewing angle without any supplementary devices [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For the reconstruction process, there are also two types of reconstruction methods, optical integral imaging reconstruction (OIIR) [2][3][4][5] and computational integral imaging reconstruction (CIIR) [6][7][8][9][10]. In OIIR, images of 3D objects are optically reconstructed from the picked-up elemental images by the combined use of a display panel and a lenslet array.…”
Section: Introductionmentioning
confidence: 99%